2021
DOI: 10.3390/antibiotics10121553
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Herpes Simplex Virus Efficacy of Silk Cocoon, Silkworm Pupa and Non-Sericin Extracts

Abstract: Herpes simplex virus (HSV) infections are prevalent worldwide and are the cause of life- threatening diseases. Standard treatment with antiviral drugs, such as acyclovir, could prevent serious complications; however, resistance has been reported specifically among immunocompromised patients. Therefore, the development of an alternative approach is needed. The silk cocoon derived from silkworm, Bombyx mori, has been recognized for its broad-spectrum biological activity, including antiviral activity; however, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Silk cocoons and silkworm pupae were provided by Piankusol Silk and Cotton Co., Ltd., Chiang Mai, Thailand. The extracts of silk cocoons with pupae and silk cocoons without pupae were boiled in sterile, distilled water at 100 °C for 9 h and 12 h. Silkworm pupae extract was boiled in sterile, distilled water at 100 °C for 1 h ( Jantakee et al, 2021 ). The sample and solvent were used at a ratio of 1:25 (weight per volume).…”
Section: Methodsmentioning
confidence: 99%
“…Silk cocoons and silkworm pupae were provided by Piankusol Silk and Cotton Co., Ltd., Chiang Mai, Thailand. The extracts of silk cocoons with pupae and silk cocoons without pupae were boiled in sterile, distilled water at 100 °C for 9 h and 12 h. Silkworm pupae extract was boiled in sterile, distilled water at 100 °C for 1 h ( Jantakee et al, 2021 ). The sample and solvent were used at a ratio of 1:25 (weight per volume).…”
Section: Methodsmentioning
confidence: 99%
“…The bioactive components of this portion of the extract were further shown to be gallic acid, flavonoids, and xanthophyll, and they played important roles in the antiviral activity. This study indicated that the SC extract has potential as a therapeutic treatment for herpes simplex virus (HSV) infection [21].…”
Section: Antiviral and Antimicrobial Effectsmentioning
confidence: 99%
“…Concurrently, the ability to modulate inflammatory responses [12][13][14] and resist oxidative stress [15][16][17][18] broadens their application in disease prevention and treatment. Furthermore, the inherent antimicrobial [4,19,20] and antiviral [21] properties of these proteins enhance their effectiveness in developing cutting-edge medical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…278 In established treatments, famciclovir presents as a viable option for managing genital herpes. 275,279 The evolving…”
Section: Current Antiviral Therapies For Hsv Infectionmentioning
confidence: 99%
“…As we delve into the complexities of this challenge, it is evident that innovative strategies are being developed, including those directed at managing acyclovir‐resistant herpes simplex keratitis 278 . In established treatments, famciclovir presents as a viable option for managing genital herpes 275,279 . The evolving research landscape emphasises the need for a holistic approach that harnesses existing antiviral agents and potential novel therapies, ensuring a practical stance against HSV infections and their adaptive resistance dynamics.…”
Section: Therapeutic Approaches and Future Directionsmentioning
confidence: 99%